PGE2 Augments Inflammasome Activation and M1 Polarization in Macrophages Infected With Salmonella Typhimurium and Yersinia enterocolitica - Sheppe, Austin E. F.; Kummari, Evangel; Walker, Alyssa; Richards, Angela; Hui, Winnie W.; Lee, Jung Hwa; Mangum, Lauren; Borazjani, Abdolsamad; Ross, Matthew K.; Edelmann, Mariola J. (Frontiers in Microbiology, 2018)
Eicosanoids are cellular metabolites, which shape the immune response, including inflammatory processes in macrophages. The effects of these lipid mediators on inflammation and bacterial pathogenesis are not clearly understood. Certain eicosanoids are suspected to act as molecular sensors for the recruitment of neutrophils, while others regulate bacterial uptake. In this study, gene expression analyses indicated that genes involved in eicosanoid biosynthesis including COX-1, COX-2, DAGL, and PLA-2 are differentially regulated in THP-1 human macrophages infected with Salmonella enterica Typhimurium or Yersinia enterocolitica. By using targeted metabolomics approach, we found that the eicosanoid precursor, arachidonic acid (AA) as well as its derivatives, including prostaglandins (PGs) PGF2α or PGE2/PGD2, and thromboxane TxB2, are rapidly secreted from macrophages infected with these Gram-negative pathogenic bacteria. The magnitude of eicosanoid biosynthesis in infected host cells depends on the presence of virulence factors of Y. enterocolitica and S. Typhimurium strains, albeit in an opposite way in Y. enterocolitica compared to S. Typhimurium infection. Trials with combinations of EP2/EP4 PGE2 receptor agonists and antagonists suggest that PGE2 signaling in these infection models works primarily through the EP4 receptor. Downstream of EP4 activation, PGE2 enhances inflammasome activation and represses M2 macrophage polarization while inducing key M1-type markers. PGE2 also led to a decreased numbers of Y. enterocolitica within macrophages. To summarize, PGE2 is a potent autocrine/paracrine activator of inflammation during infection in Gram-negative bacteria, and it affects macrophage polarization and function, likely controlling bacterial clearance by macrophages.